DENTIFICATION AND CLASSIFICATION OF SOIL TYPES IN THE SERANG REGION USING Vs30 GEOMORPHOLOGICAL DATA: IDENTIFIKASI KLASIFIKASI JENIS TANAH DI WILAYAH SERANG MENGGUNAKAN DATA Vs 30 GEOMORFOLOGI - Selsa Sururiyah Sya’baniah; Agus Setyo Budi; Nur Fani Habibah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
This study aims to identify and classify soil types in the Serang area using geomorphology-based Vs30 data as the main parameter. The geomorphological method analyzes the physical characteristics and morphology of soils, while Vs30 measures shear wave velocity to a depth of 30 meters to evaluate soil strength and stability. The geomorphology map and Vs30 map are interconnected to comprehensively present soil distribution and properties. The Indonesian Local Footprint Atlas (Vs30) prepared by PVMBG, using engineering geomorphology classification, is the main reference in this study to create seismic/earthquake hazard maps in Serang. The results show a close relationship between Vs30 and geomorphology, which includes variations in soil texture, structure and geotechnical conditions in Serang. This information is critical for land use planning, disaster mitigation and resource management. The research highlights the importance of Vs30 data in producing accurate data, where soil class affects earthquake acceleration and intensity. Determination of soil class using geological and morphological parameters and Vs30, classified according to SNI standards, is an important step in earthquake risk management in this region.